ELEVATE-LNP: Empty lipid nanoparticle enabled validation and AI-guided therapeutic evaluation for efficient formulation optimization for mRNA delivery - Mingzhi Yu; Luhan Wang; Timothy Elliott; Xianqing Wang; Allen Mathew; Bei Qiu; Liang Yao; Wenxin Wang; Nan Zhang (Chemical Engineering Journal, 2026)

Secondary consumption of mycorrhizal fungi by two endangered marsupial carnivores: the spotted-tailed quoll (Dasyurus maculatus) and Tasmanian devil (Sarcophilus harrisii) - Conor Nest; Timothy Henderson; Todd F. Elliott; Guy-Anthony Ballard; Karl Vernes (Oecologia, 2026)
Mycorrhizal fungi form symbiotic relationships that are vital to nutrient and water acquisition by plants, with many mycorrhizal fungi requiring animal-mediated dispersal. Primary mycophagists often have relatively small home ranges, meaning fungal dispersal distances can be relatively short. However, fungal spores can be incidentally consumed and dispersed when a predator or scavenger eats mycophagous prey. These secondary consumers often move greater distances than their prey, which enables the long-distance dispersal (LDD) of fungal spores. In this study, we aimed to determine whether Australia’s two largest extant marsupial carnivores, the spotted-tailed quoll ( Dasyurus maculatus ) and Tasmanian devil ( Sarcophilus harrisii ), are acting as secondary dispersers of mycorrhizal fungi through the consumption of mycophagous prey. Quoll trapping and scat collection was undertaken at three sites in eastern New South Wales, whilst Tasmanian devil scats were collected opportunistically at three sites in Tasmania. Scats from these predators were analysed for the presence of fungal spores and prey animals. Quolls consumed 20 mammal species, including 14 that were identified as mycophagous. Across all three sites, 72.3% of quoll scats contained fungi, with a total of 77 fungal taxa identified. Quoll scats containing mycophagous mammals contained significantly more fungal taxa than those without mycophagous mammals present. Tasmanian devil scats contained six fungal taxa, with 33% of scats containing fungi, but a small sample size precluded further analysis. Our study indicates that spotted-tailed quolls and Tasmanian devils are both likely to be providing a previously unreported ecosystem service through the LDD of mycorrhizal fungi.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Environmental drivers of foraging by deep-diving cetaceans: Roles of mesoscale oceanography and light-driven cycles - Thomas A. Clay; Gemma Carroll; Megan A. Cimino; Jennifer L. Miksis-Olds; Katie A. Kowarski; Anthony P. Lyons; Peter I. Miller; Timothy S. Moore; Joseph D. Warren; Elliott L. Hazen (Progress in Oceanography, 2025)

Child and non-child-targeted food and beverage advertisements on child television in two policy environments in Canada - Julia Soares Guimaraes; Meghan Pritchard; Grace Gillis; Mariangela Bagnato; Lauren Remedios; Soulene Sabir; Lana Vanderlee; Timothy Ramsay; Charlene Elliott; Monique Potvin Kent (Appetite, 2025)

Actor-network analysis of partners facilitating regenerative ranching practices in the US Northern Great Plains - Timothy Pape; Gwendŵr Meredith; David Sandahl; Md Faizul Kabir; Simanti Banerjee; Craig Allen; Elliott Dennis; Mitchell Stephenson (Rangelands, 2025)

Thermal treatment of lizardite for mineral carbonation using high flux radiation - Elliott Lewis; Zachary Wetzler; Gule Li; Woei Saw; Graham Nathan; Eric Kennedy; Michael Stockenhuber; Timothy Oliver; Alfonso Chinnici (Fuel, 2025)

Knowledge co-production for identifying indicators and prioritising solutions for food and land system sustainability in Australia - Romy L. Zyngier; Carla L. Archibald; Brett A. Bryan; Haley Lambert; Enayat A. Moallemi; Mark Elliott; Mark Lawrence; Jane Hutchinson; Lauren T. Bennett; Timothy Reeves; Matthew Pryor; Ulrika Lindholm; et al. (Sustainability Science, 2024)
Achieving sustainable Australian food and land systems requires the rapid implementation and scaling up of a broad suite of solutions to meet the Sustainable Development Goals (SDGs). Decision-making frameworks are needed to identify suitable indicators and prioritise solutions at national scales to inform sustainability transitions. Using a knowledge co-production framework, we convened 150 stakeholders from 100 + organisations to identify 18 nationally relevant indicators that aligned with critical SDGs describing a sustainable food and land system for Australia, in addition to 78 key solutions (supply- and demand-side) to enable progress against these indicators. We then asked subject matter experts to code the impact of each solution on each indicator using an adapted interaction mapping method accounting for uncertainty. The solution category ‘Protecting and restoring nature’, which included solutions targeting conservation and restoration, showed the highest potential for capturing synergies and avoiding trade-offs across multiple indicators. This category exhibited 34.6% of total major synergies, supporting the achievement of clean water and sanitation (SDG6), economic growth (SDG12), life under water (SDG14), and life on land (SDG15). The solution category ‘Carbon sequestration’, which included technological and biological carbon dioxide removal solutions, had the highest number of trade-offs with individual sustainability indicators (42.3%), particularly those relating to zero hunger (SDG2), wellbeing (SDG3), SDG6, SDG14, and SDG15. Our framework can be used to inform future research investment, support the prioritisation of solutions for quantitative modelling, and inform discussions with stakeholders and policymakers for transforming national-scale food and land systems in alignment with the SDGs.

Advancing Understanding of Chemical Exposures and Maternal-child Health Through the U.S. Environmental Influences on Child Health Outcomes (ECHO) Program: A Scoping Review - Emily S. Barrett; Jennifer L. Ames; Stephanie M. Eick; Alicia K. Peterson; Zorimar Rivera-Núñez; Anne P. Starling; Jessie P. Buckley; Barbara O‟Brien; Lisa Peterson; Patrick Parsons; Kannan Kurunthacalam; Manish Arora; et al. (Current Environmental Health Reports, 2024)
Purpose of Review Environmental chemical exposures may disrupt child development, with long-lasting health impacts. To date, U.S. studies of early environmental exposures have been limited in size and diversity, hindering power and generalizability. With harmonized data from over 60,000 participants representing 69 pregnancy cohorts, the National Institutes of Health’s Environmental influences on Child Health Outcomes (ECHO) Program is the largest study of U.S. children’s health. Here, we: (1) review ECHO-wide studies of chemical exposures and maternal-child health; and (2) outline opportunities for future research using ECHO data. Recent Findings As of early 2024, in addition to over 200 single-cohort (or award) papers on chemical exposures supported by ECHO, ten collaborative multi-cohort papers have been made possible by ECHO data harmonization and new data collection. Multi-cohort papers have examined prenatal exposure to per- and polyfluoroalkyl substances (PFAS), phthalates, phenols and parabens, organophosphate esters (OPEs), metals, melamine and aromatic amines, and emerging contaminants. They have primarily focused on describing patterns of maternal exposure or examining associations with maternal and infant outcomes; fewer studies have examined later child outcomes (e.g., autism) although follow up of enrolled ECHO children continues. The NICHD’s Data and Specimen Hub (DASH) database houses extensive ECHO data including over 470,000 chemical assay results and complementary data on priority outcome areas (pre, peri-, and postnatal, airway, obesity, neurodevelopment, and positive health), making it a rich resource for future analyses. Summary ECHO’s extensive data repository, including biomarkers of chemical exposures, can be used to advance our understanding of environmental influences on children’s health. Although few published studies have capitalized on these unique harmonized data to date, many analyses are underway with data now widely available.

Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

Dynamic human, oceanographic, and ecological factors mediate transboundary fishery overlap across the Pacific high seas - Timothy H. Frawley; Barbara Muhling; Stephanie Brodie; Hannah Blondin; Heather Welch; Martin C. Arostegui; Steven J. Bograd; Camrin D. Braun; Megan A. Cimino; Nima Farchadi; Elliott L. Hazen; Desiree Tommasi; et al. (Fish and Fisheries, 2024)
The management and conservation of tuna and other transboundary marine species have to date been limited by an incomplete understanding of the oceanographic, ecological and socioeconomic factors mediating fishery overlap and interactions, and how these factors vary across expansive, open ocean habitats. Despite advances in fisheries monitoring and biologging technology, few attempts have been made to conduct integrated ecological analyses at basin scales relevant to pelagic fisheries and the highly migratory species they target. Here, we use vessel tracking data, archival tags, observer records, and machine learning to examine inter‐ and intra‐annual variability in fisheries overlap (2013–2020) of five pelagic longline fishing fleets with North Pacific albacore tuna ( Thunnus alalunga , Scombridae). Although progressive declines in catch and biomass have been observed over the past several decades, the North Pacific albacore is one of the only Pacific tuna stocks primarily targeted by pelagic longlines not currently listed as overfished or experiencing overfishing. We find that fishery overlap varies significantly across time and space as mediated by (1) differences in habitat preferences between juvenile and adult albacore; (2) variation of oceanographic features known to aggregate pelagic biomass; and (3) the different spatial niches targeted by shallow‐set and deep‐set longline fishing gear. These findings may have significant implications for stock assessment in this and other transboundary fishery systems, particularly the reliance on fishery‐dependent data to index abundance. Indeed, we argue that additional consideration of how overlap, catchability, and size selectivity parameters vary over time and space may be required to ensure the development of robust, equitable, and climate‐resilient harvest control rules.

Projecting climate change impacts from physics to fisheries: A view from three California Current fisheries - James A. Smith; Mercedes Pozo Buil; Barbara Muhling; Desiree Tommasi; Stephanie Brodie; Timothy H. Frawley; Jerome Fiechter; Stefan Koenigstein; Amber Himes-Cornell; Michael A. Alexander; Steven J. Bograd; Nathalí Cordero Quirós; et al. (Progress in Oceanography, 2023)

Molecular Response of the Brain to Cross-Generational Warming in a Coral Reef Fish - Moisés A. Bernal; Elliott Schmidt; Jennifer M. Donelson; Philip L. Munday; Timothy Ravasi (Frontiers in Marine Science, 2022)
Ocean warming is a threat to marine biodiversity, as it can push marine species beyond their physiological limits. Detrimental effects can occur when marine poikilotherms are exposed to conditions beyond their thermal optima. However, acclamatory mechanisms, such as plasticity, may enable compensation of detrimental effects if warming is experienced during development or across generations. Studies evaluating the molecular responses of fishes to warming have mostly focused on liver, muscle, and gonads, and little is known about the effects on other vital organs, including the brain. This study evaluated the transcriptional program of the brain in the coral reef fish Acanthochromis polyacanthus , exposed to two different warming scenarios: +1.5°C and +3.0°C, across successive generations. Fish were exposed to these conditions in both developmental (F1 and F2) and transgenerational settings (F2 only), as well as a treatment with step-wise warming between generations. The largest differences in gene expression were between individuals of the first and second generation, a pattern that was corroborated by pairwise comparisons between Control F1 and Control F2 (7,500 DEGs) fish. This large difference could be associated with parental effects, as parents of the F1 generation were collected from the wild, whereas parents of the F2 generation were reared in captivity. A general response to warming was observed at both temperatures and in developmental and transgenerational treatments included protein folding, oxygen transport (i.e., myoglobin), apoptosis and cell death, modification of cellular structure, mitochondrial activity, immunity and changes in circadian regulation. Treatments at the highest temperature showed a reduction in synaptic activity and neurotransmission, which matches previous behavioral observations in coral reef fishes. The Transgenerational +3.0°C treatment showed significant activation of the gene pls3 , which is known for the development of neuro-muscular junctions under heat-stress. F2 samples exposed to step-wise warming showed an intermediate response, with few differentially expressed genes compared to developmental and transgenerational groups (except for Transgenerational +1.5°C). In combination with previous studies on liver gene expression, this study indicates that warming produces a molecular signature of stress response in A. polyacanthus that is influenced both by the intensity of warming as well as the duration of exposure.

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Changes to the structure and function of an albacore fishery reveal shifting social‐ecological realities for Pacific Northwest fishermen - Timothy H. Frawley; Barbara A. Muhling; Stephanie Brodie; Mary C. Fisher; Desiree Tommasi; Gwendal Le Fol; Elliott L. Hazen; Stephen S. Stohs; Elena M. Finkbeiner; Michael G. Jacox (Fish and Fisheries, 2021)
Marine fisheries around the globe are increasingly exposed to external drivers of social and ecological change. Though diversification and flexibility have historically helped marine resource users negotiate risk and adversity, much of modern fisheries management treats fishermen as specialists using specific gear types to target specific species. Here, we describe the evolution of harvest portfolios amongst Pacific Northwest fishermen over 35+ years with explicit attention to changes in the structure and function of the albacore ( Thunnus alalunga, Scombridae) troll and pole‐and‐line fishery. Our analysis indicates that recent social–ecological changes have had heterogenous impacts upon the livelihood strategies favoured by different segments of regional fishing fleets. As ecological change and regulatory reform have restricted access to a number of fisheries, many of the regional small ( 60 ft) targeting albacore are more specialized now than previously observed, even as participation in multiple fisheries has become increasingly common for this size class. In describing divergent trajectories associated with the albacore fishery, one of the US West Coast's last open‐access fisheries, we highlight the diverse strategies and mechanisms utilized to sustain fisheries livelihoods in the modern era while arguing that alternative approaches to management and licensing may be required to maintain the viability of small‐scale fishing operations worldwide moving forward.

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Physiological effects of dissolved oxygen are stage-specific in incubating Atlantic salmon (Salmo salar) - Andrew T. Wood; Timothy D. Clark; Nicholas G. Elliott; Peter B. Frappell; Sarah J. Andrewartha (Journal of Comparative Physiology B, 2019)

Large-scale invasion of western Atlantic mesophotic reefs by lionfish potentially undermines culling-based management - Dominic A. Andradi-Brown; Mark J. A. Vermeij; Marc Slattery; Michael Lesser; Ivonne Bejarano; Richard Appeldoorn; Gretchen Goodbody-Gringley; Alex D. Chequer; Joanna M. Pitt; Corey Eddy; Struan R. Smith; Eran Brokovich; et al. (Biological Invasions, 2017)

The violation of Fitts’ Law: an examination of displacement biases and corrective submovements - James W. Roberts; Jarrod Blinch; Digby Elliott; Romeo Chua; James L. Lyons; Timothy N. Welsh (Experimental Brain Research, 2016)

Evidence for Alzheimer’s disease-linked synapse loss and compensation in mouse and human hippocampal CA1 pyramidal neurons - Krystina M. Neuman; Elizabeth Molina-Campos; Timothy F. Musial; Andrea L. Price; Kwang-Jin Oh; Malerie L. Wolke; Eric W. Buss; Stephen W. Scheff; Elliott J. Mufson; Daniel A. Nicholson (Brain Structure and Function, 2015)

The determinants of serum vitamin D levels in participants in a melanoma case–control study living in a temperate climate - John R. Davies; Yu-Mei Chang; Helen Snowden; May Chan; Susan Leake; Birute Karpavicius; Sue Haynes; Kairen Kukalizch; Juliette Randerson-Moor; Faye Elliott; Julian Barth; Peter A. Kanetsky; et al. (Cancer Causes & Control, 2011)

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

Between-trial inhibition and facilitation in goal-directed aiming: manual and spatial asymmetries - Luc Tremblay; Timothy N. Welsh; Digby Elliott (Experimental Brain Research, 2005)

A prevalent POLG CAG microsatellite length allele in humans and African great apes - Anja T. Rovio; Josef Abel; Arja L. Ahola; Aida M. Andres; Jaume Bertranpetit; Antoine Blancher; Ronald E. Bontrop; Leona G. Chemnick; Howard J. Cooke; James M. Cummins; Heidi A. Davis; David J. Elliott; et al. (Mammalian Genome, 2004)

The Mller-Lyer illusion affects the planning and control of manual aiming movements - Daniel V. Meegan; Cheryl M. Glazebrook; Victoria P. Dhillon; Luc Tremblay; Timothy N. Welsh; Digby Elliott (Experimental Brain Research, 2004)